Cinta, “Perjuangan Kelas”, dan Kekerasan: Analisis Framing Ideologi di Balik Film Televisi (FTv) di Indonesia - Refti Handini Listyani; Fransiscus Xaverius Sri Sadewo; Rachmah Ida; Emy Susanti (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2022)
This research examines what ideologies Film Television (FTv) offered during the COVID-19 pandemic and how these ideologies developed in the FTv using framing analysis and a gender perspective approach. Results indicate that there are two hidden ideologies as follows. First, the FTv production house carries a patriarchal ideology by raising themes that discriminate against women through stereotypes against women that appear in the story. Second, the FTv production house carries the ideology of feminism, with themes that position women as superordinate. Women occupy a higher social class than men. Women determine their own lives; even women have power over men. Academically, these findings are expected to add to the theoretical study in the sociology of communication and media research on how the power of knowledge in FTv affects the audience and contributes information, and enriches the development of research on gender relations and violence.